OPTIMALISASI OPERASI PENANGKAPAN IKAN GILLNET DI PPN PEKALONGAN JAWA TENGAH - Eko Sri Wiyono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
Fishing activities is a high risk activity and contains high uncertainty. Tomanage the fisheries to be sustainable, we need a study on the factors thatinfluence the success of fishing operations. To answer these problems, we haveconduct research on gillnet fishing gear in Pekalongan Fishing Port. The results ofthis study showed that the long days at sea and number of hauling factorsaffecting total catches. Long days at sea have elasticity -0.854 while the numberof hauling has elasticity 2,158. Overall, the rate of return to scale in theproduction function equation produces 1,304 value and categorized as increasingreturns to scale.Keywords: eficiency, gillnet, factors of production, Pekalongan.